Long-term outcomes in patients with PET-predicted poor-responsive HER2-positive breast cancer treated with neoadjuvant bevacizumab added to trastuzumab and docetaxel: 5-year follow-up of the randomised Avataxher study. (November 2020) - Coudert, Bruno; Pierga, Jean-Yves; Mouret-Reynier, Marie-Ange; Kerrou, Kaldoun; Ferrero, Jean-Marc; Petit, Thierry; Du, Fanny Le; Dupré, Pierre-François; Bachelot, Thomas; Gabelle, Philippe; Chauvet, Marie-Pierre; Coeffic, David; et al.
Abstract: Background: The open-label, randomised Phase 2 AVATAXHER study (NCT01142778) demonstrated that early PET assessment identified HER2-positive breast cancer patients who responded poorly to neoadjuvant docetaxel plus trastuzumab. Adding neoadjuvant bevacizumab for PET-predicted poor-responders improved pathological complete response (pCR) rates (43.8% vs 24.0%). We investigated long-term study outcomes. Methods: Patients were treated in three groups. All patients initially received two cycles of standard neoadjuvant therapy with [¹⁸F]-FDG PET conducted before each cycle. Those with ≥70% change in the maximum standardised uptake value (∆SUVmax) received four further cycles of standard neoadjuvant therapy (PET responders). PET-predicted poor-responders (∆SUVmax <70%) were randomised (2:1) to neoadjuvant therapy with (Group A) or without (Group B) bevacizumab for cycles 3–6. All patients received one further cycle of trastuzumab before surgery plus adjuvant trastuzumab (11 cycles). Findings: 142 patients were randomized and treated (PET responders, n  = 69; Group A, n  = 48; Group B, n  = 25). 5-year disease-free survival rates were 90.5% (95% CI: 80.0–95.6%) in PET responders, 90.2% (95% CI: 75.9–96.2%) in Group A, and 76.0% (95% CI: 54.2–88.4%) in Group B. However, no difference was observed between randomised arms in a sensitivity analysis. During adjuvant therapy, the incidence of Grade ≥3 (Group A: 25.6%; Group B 12.5%) and serious adverse events (Group A: 18.6%; Group B 12.5%) was higher in Group A vs Group B, but with no apparent effect on cardiac events. Interpretation: In patients with HER2-positive breast cancer, an intervention based on early PET assessment and improvement of pCR does not modify disease-free survival. Funding: Roche France.